Implementasi Restorative Justice dalam Pemulihan Ekonomi Nasional: Upaya Mewujudkan Peradilan yang Humanis (Studi terhadap Rumah Restorative Justice Bojonegoro) - Lisa Aminatul Mukaromah; Eko Arief Cahyono; Dery Ariswanto; Khurul Anam (UNES Law Review, 2023)
This study focuses on efforts to determine the practice of solving criminal cases through the Restorative Justice approach at the House of Restorative Justice in Bojonegoro Regency. This research uses qualitative methods and field research to explore the concept of restorative justice and its application to the House of Restorative Justice in Bojonegoro Regency. The results of this study state that Restorative Justice is a powerful alternative paradigm for solving minor criminal cases in the community. The Bojonegoro Regency Government, together with the District Attorney's Office, collaborate in humane law enforcement through the establishment of 5 (five) House of Restorative Justices in Bojonegoro Regency located in Kauman Village and Pacul Village in Bojonegoro District, Jipo Village, Kepohbaru District, Dolokgede Village, Tambakrejo District, and Pilanggede Village, Balen District. The application of the concept of restorative Justice at the House of Restorative Justice in Bojonegoro has generally been carried out well as a form of the sense of crisis towards social problems of the community in a humane law enforcement effort. It involves the active role of village heads and local community leaders.